2017
DOI: 10.1038/s41598-017-02737-6
|View full text |Cite
|
Sign up to set email alerts
|

Trichogenic-selenium nanoparticles enhance disease suppressive ability of Trichoderma against downy mildew disease caused by Sclerospora graminicola in pearl millet

Abstract: Trichoderma spp. are well known biocontrol agents used against phytopathogens. In the present work Trichoderma-mediated Selenium nanoparticles (SeNPs) were synthesized and extent of downy mildew (DM) disease control in pearl millet (PM) was studied. Six species of Trichoderma namely, T. asperellum, T. harzianum, T. atroviride, T. virens, T. longibrachiatum and T. brevicompactum were evaluated in the form of culture filtrate (CF), cell lysate (CL) and crude cell wall (CW) to synthesize SeNPs. All these componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 65 publications
6
45
1
Order By: Relevance
“…Later, the leaves were cut into small pieces and petri dishes lined were with a wet double layer of blotter discs and the plates were incubated at 20 • C and 95% relative humidity (RH) in the dark overnight. In the early morning, sporangia produced on the leaves were harvested into sterile distilled water (SDW) and the spore load was adjusted to 4 × 10 4 zoospores mL −1 using a hemocytometer, and used as a source of inoculum, according to Nandini et al [23]. and T. brevicompactum (UP-91: KM100836)) used in the study were collected from the culture collection of the D.O.S in Biotechnology, University of Mysore.…”
Section: Host Pathogen and Inoculum Preparationmentioning
confidence: 99%
“…Later, the leaves were cut into small pieces and petri dishes lined were with a wet double layer of blotter discs and the plates were incubated at 20 • C and 95% relative humidity (RH) in the dark overnight. In the early morning, sporangia produced on the leaves were harvested into sterile distilled water (SDW) and the spore load was adjusted to 4 × 10 4 zoospores mL −1 using a hemocytometer, and used as a source of inoculum, according to Nandini et al [23]. and T. brevicompactum (UP-91: KM100836)) used in the study were collected from the culture collection of the D.O.S in Biotechnology, University of Mysore.…”
Section: Host Pathogen and Inoculum Preparationmentioning
confidence: 99%
“…Groups of different microorganisms, including fungi, bacteria and yeasts, and plant extracts, are being used to produce NPs . Using this approach, Trichoderma ‐mediated Selenium nanoparticles (SeNPs) were synthesized recently and used to control downy mildew disease in pearl millet . The antimicrobial activity of those MNPs seems to occur via: (i) photocatalysis‐absorbed photons leading to the release of superoxide radicals, which cause the death of bacterial, fungal, and viral organisms by oxidation of critical molecular structures; (ii) accumulation and dissipation in the cell membrane, leading to membrane damage and release of cell contents; and (iii) uptake of metallic ions into cells followed by disruption of DNA replication …”
Section: Nanomaterials In Agriculturementioning
confidence: 99%
“…It has been reported that selenium (Se) application decreases Cd uptake [75]. In similar studies, selenium, copper, zinc oxide and many other metallic nanoparticles [92][93][94][95][96][97][98] have been studied in food processing, packaging and preservation against phytopathogens and rodents. The washing with water or soaking in solutions of salt and some chemicals e.g.…”
Section: Recommendationsmentioning
confidence: 99%